National Brand Identity: Pilot Study on Perception of Croatian Student Population - Sanja Seljan; Berislava Starešinić; Sara Horvat (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
A message sent to a specific market or an audience contains certain types of information that affect the audience. For this reason, brand identity, nowadays increasingly in a digital form, plays an important role. Each state wants to create a robust, attractive, and different brand identity that will set it apart from other states and thus augment its reputation. This research aimed to determine the elements of brand identity that respondents mostly associate with Croatia and to examine their attitudes towards the belief that the brand identity that influences emotions is essential in the creation of national visual identity, as well as their attitudes towards the assumption that the brand identity of Croatia should be liked first by the inhabitants of Croatia, and only then by foreign tourists. Two research propositions were tested using the structural equation modeling, measuring the relationship between the emotional and formal elements of brand identity with the attitudes towards the emotions concerning the brand identity and the relevance of the brand identity to the country residents.v
Keywords: M3; 330; branding; nation; brand identity; Croatia; reputation; structural equation modeling; visual brand identity; information